Integrating employability skills in engineering education - URVASHI KAUSHAL (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This paper examines the curricula and pedagogical practices of Gujarat colleges associated with the Gujarat Technical University and the National Institute of Technology, Surat, concerning the instruction of communication skills. This encompasses the vast majority of Gujarat’s engineering schools.Method: To better understand the challenges of instructing engineering students, a qualitative study was conducted in which eight English teachers from different engineering colleges in and around Surat were interviewed. To complete the research, eight English professors at different engineering schools in and around Surat, Gujarat, were contacted. These educators were chosen to represent a range of ages, levels of experience and education, and specialisations.Findings: This paper uses the study’s findings to argue that engineering curricula should incorporate several activities aimed at improving engineers’ employability. From this, we can infer that the chalk-and-talk approach to teaching engineers communication skills is ineffective. Furthermore, industry standards have increased rapidly.Implications/Novel Contribution: This research contributes to the body of literature by providing empirical evidence for the importance of fostering employability skills in one’s communication repertoire. While generalisations from this study are obviously not possible, it is safe to assume that English instructors in India’s engineering colleges face similar difficulties to those identified in this study’s sample. Second, despite efforts to improve the situation, recent engineering graduates’ lack of employability skills continues to trouble both Indian employers and graduates alike.